2018
DOI: 10.26444/aaem/86690
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of musculoskeltal system pain complaints reported by forestry workers

Abstract: The work of a forester which consist, among other things, in relocation on foot or by vehicle over long distances along an uneven terrain and in various weather conditions, is a risk factor of the occurrence of musculosceletal disorders concerning the low back and knees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
2
4
0
Order By: Relevance
“…The highest frequency of disorders is identified in the lower back, a body region that is especially affected in forestry professions, especially where lifting of heavy objects, such as the chainsaw or logs, is part of the profession (Gandaseca and Yoshimura 2001). Our finding is in line with the previous studies of Choina et al (2018) and Gallis (2006), who also reported the highest incidence of musculoskeletal disorders in the lower back area. Manual loading is associated with excessive bending and muscular exertion that primarily affect the lower back region (Verbeek et al 2012).…”
Section: Msd Prevalencesupporting
confidence: 94%
“…The highest frequency of disorders is identified in the lower back, a body region that is especially affected in forestry professions, especially where lifting of heavy objects, such as the chainsaw or logs, is part of the profession (Gandaseca and Yoshimura 2001). Our finding is in line with the previous studies of Choina et al (2018) and Gallis (2006), who also reported the highest incidence of musculoskeletal disorders in the lower back area. Manual loading is associated with excessive bending and muscular exertion that primarily affect the lower back region (Verbeek et al 2012).…”
Section: Msd Prevalencesupporting
confidence: 94%
“…It was found that workers who are exposed to WBV have an increased risk of lower back pain. These results are like those obtained by Choina [3], where pain complaints of forestry workers were analysed. The results revealed that the largest percentage of forestry workers complain about lower part spine pain, which is mainly caused by WBV.…”
Section: Introductionsupporting
confidence: 89%
“…Today, these pathologies are ranked first among those recorded and refunded, both in Italy and Europe [22,33,35,36]: among them, the mostly spread are the carpal tunnel syndrome, epichondilitis, rotatory cuff tunnel syndrome and lombo-sacral rachis pathologies [19,20,[31][32][33][34]37].…”
Section: Discussionmentioning
confidence: 99%